2010
DOI: 10.4049/jimmunol.0902522
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell Inhibition Is Connected to Exhaustion of CD8+ T Cell Polyfunctionality during Chronic Hepatitis C Virus Infection

Abstract: Material Supplementary 2.DC1http://www.jimmunol.org/content/suppl/2010/02/15/jimmunol.090252

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 48 publications
3
41
0
3
Order By: Relevance
“…Dysfunctional DCs are involved in the exhaustion of CD8 ? T cells, confirming that DCs play an important role in linking the innate immune system to the adaptive immune system [82] Monocyte-derived DCs generated from hepatitis C patients have been shown to have an impaired ability to stimulate allogeneic CD4 T cells [83,84], with a decrease in the functional impairment of DCs when HCV was eradicated from patients, thereby providing evidence for HCV-induced DC disability [83]. NK cells from HCV-infected patients are able to downregulate DC functions in the presence of hepatocytes by secreting the suppressive cytokines IL-10 and transforming growth factor beta-1 [85].…”
Section: Dcs In Chronic Hcv Infectionmentioning
confidence: 68%
“…Dysfunctional DCs are involved in the exhaustion of CD8 ? T cells, confirming that DCs play an important role in linking the innate immune system to the adaptive immune system [82] Monocyte-derived DCs generated from hepatitis C patients have been shown to have an impaired ability to stimulate allogeneic CD4 T cells [83,84], with a decrease in the functional impairment of DCs when HCV was eradicated from patients, thereby providing evidence for HCV-induced DC disability [83]. NK cells from HCV-infected patients are able to downregulate DC functions in the presence of hepatocytes by secreting the suppressive cytokines IL-10 and transforming growth factor beta-1 [85].…”
Section: Dcs In Chronic Hcv Infectionmentioning
confidence: 68%
“…In contrast to acute infection, optimal polyfunctional memory T cell responses are lost in chronic infections and cancer, both in humans and mice (5,8,9). These cells have been characterized as "exhausted" (8,10) and factors promoting the development of T cell exhaustion include persistent and high levels of antigen stimulation (11,12), DC inhibition (3), and upregulation of inhibitory receptors, such as PD-1, on T cells (13)(14)(15)(16)(17). While recent work has highlighted a role for PD-1 and other inhibitory receptors in T cell exhaustion, blockade of inhibitory receptor signaling in HIV-specific T cells had only a moderate effect in reversing the exhaustion phenotype and increasing T cell polyfunctionality (14,15), thus indicating that additional molecular mechanisms are involved in the inhibition of T cell polyfunctionality.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the enhanced infection of DCs, followed by reduced T cell stimulatory capacity, is probably one of the mechanisms by which chronic pathogens initiate immunosuppression within the host (79,80). More interestingly, independent of preferential DC infection by chronic pathogens, it has been reported that the functional impairment of DCs is associated with the exhaustion of T cell function and progression of disease during HIV, HBV, HCV, and LCMV infections (81)(82)(83)(84)(85)(86). However, the molecular mechanisms underlying impaired T cell function mediated by DCs during chronic pathogen infection have to be fully elucidated.…”
Section: Extrinsic Factors Regulating T Cell Immunity In a Chronic Anmentioning
confidence: 99%